Heterogeneity of Cell Surface Glutamate and GABA Receptor Expression in Shank and CNTN4 Autism Mouse Models - Heise, Christopher; Preuss, Jonathan M.; Schroeder, Jan C.; Battaglia, Chiara R.; Kolibius, Jonas; Schmid, Rebecca; Kreutz, Michael R.; Kas, Martien J. H.; Burbach, J. Peter H.; Boeckers, Tobias M. (Frontiers in Molecular Neuroscience, 2018)
Autism spectrum disorder (ASD) refers to a large set of neurodevelopmental disorders, which have in common both repetitive behavior and abnormalities in social interactions and communication. Interestingly, most forms of ASD have a strong genetic contribution. However, the molecular underpinnings of this disorder remain elusive. The SHANK3 gene (and to a lesser degree SHANK2) which encode for the postsynaptic density (PSD) proteins SHANK3/SHANK2 and the CONTACTIN 4 gene which encodes for the neuronal glycoprotein CONTACTIN4 (CNTN4) exhibit mutated variants which are associated with ASD. Like many of the other genes associated with ASD, both SHANKs and CNTN4 affect synapse formation and function and are therefore related to the proper development and signaling capability of excitatory and inhibitory neuronal networks in the adult mammal brain. In this study we used mutant/knock-out mice of Shank2 (Shank2-/-), Shank3 (Shank3αβ-/-), and Cntn4 (Cntn4-/-) as ASD-models to explore whether these mice share a molecular signature in glutamatergic and GABAergic synaptic transmission in ASD-related brain regions. Using a biotinylation assay and subsequent western blotting we focused our analysis on cell surface expression of classical several ionotropic glutamate and GABA receptor subunits: GluA1, GluA2, and NR1GluN1 were analyzed for excitatory synaptic transmission, and the α1 subunit of the GABAA receptor was analyzed for inhibitory synaptic transmission. We found that both Shank2-/- and Shank3αβ-/- mice exhibit reduced levels of several cell surface glutamate receptors in most of the analyzed brain regions – especially in the striatum and thalamus – when compared to wildtype controls. Interestingly, even though Cntn4-/- mice also show reduced levels of some cell surface glutamate receptors in the cortex and hippocampus, increased levels of cell surface glutamate receptors were found in the striatum. Moreover, Cntn4-/- mice do not only show brain region-specific alterations in cell surface glutamate receptors but also a downregulation of cell surface GABA receptors in several of the analyzed brain regions. The results of this study suggest that even though mutations in defined genes can be associated with ASD this does not necessarily result in a common molecular phenotype in surface expression of glutamatergic and GABAergic receptor subunits in defined brain regions.